2020
DOI: 10.26508/lsa.201900534
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1 coordinates energy metabolism and differentiation of pluripotent stem cells

Abstract: BMAL1 is essential for the regulation of circadian rhythms in differentiated cells and adult stem cells, but the molecular underpinnings of its function in pluripotent cells, which hold a great potential in regenerative medicine, remain to be addressed. Here, using transient and permanent loss-of-function approaches in mouse embryonic stem cells (ESCs), we reveal that although BMA L1 is dispensable for the maintenance of the pluripotent state, its depletion leads to deregulation of transcriptional programs lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Bmal1 also plays an essential role in regulating the differentiation potential of embryonic stem cells (ESCs). Loss of Bmal1 function results in a shift from glycolytic to oxidative metabolism through the dysregulation of metabolic gene expression [76]. These results indicate that Bmal1 has a non-canonical circadian function, i.e., to regulate metabolic reprogramming in ESCs.…”
Section: Core Circadian Clock Genes and Metabolismmentioning
confidence: 89%
See 1 more Smart Citation
“…Bmal1 also plays an essential role in regulating the differentiation potential of embryonic stem cells (ESCs). Loss of Bmal1 function results in a shift from glycolytic to oxidative metabolism through the dysregulation of metabolic gene expression [76]. These results indicate that Bmal1 has a non-canonical circadian function, i.e., to regulate metabolic reprogramming in ESCs.…”
Section: Core Circadian Clock Genes and Metabolismmentioning
confidence: 89%
“…The levels of ROS in tissues are closely associated with hair follicle regeneration. Loss of the circadian clock in stem cells can also result in a significant increase in ROS production [76]. Furthermore, normal mitochondrial function cannot be maintained in Bmal1-deficient, M1-activated macrophages [11,18,80,103].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, coupling efficiency was increased in mice of the Bmal1 line when compared to mice of the Gpr88 line, presumably through reduced proton leakage in Bmal1 cKO and CTRL mice, indicating that the deletion of one copy of Bmal1 in the striatum is sufficient to cause these alterations. Conversely, a study on embryonic stem cells with a Bmal1 knockout revealed higher respiration accompanied by increased proton leakage and increased mitochondrial ROS production ( Ameneiro et al, 2020 ). The effects, however, may be linked to a specific role of Bmal1 on cell functions during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In mice with a dysfunctional circadian clock, the daily cycle of OXPHOS is abolished, suggesting that there is an intrinsic dependence of the mitochondrial respiration complexes on the circadian clockwork ( Neufeld-Cohen et al, 2016 ). Deletion of arntl in C2C12 myotubes causes a reduction of both OXPHOS and extracellular acidification rate (an indicator of glycolytic rate), but deletion in embryonic stem cells increases OXPHOS while reducing glycolytic rate ( Ameneiro et al, 2020 ; Peek et al, 2017 ). This suggests there is tissue specificity in the effect of ‘circadian clock knockout’ on mitochondrial responses.…”
Section: Introductionmentioning
confidence: 99%